Health of Black and LGBTQIA+ Populations in Health EDUCATION: A Scoping Review Protocol - Bruno Pereira da Silva; Patrícia de Carvalho Nagliate; Gabriel da Silva Brito; Danilo Bonfim de Queiroz; Ana Paula de Morais e Oliveira; Célia Alves Rozendo; Danielly Santos dos Anjos Cardoso; Roberto Ariel Abeldaño Zuñiga; Paula Cristina Pereira da Costa; Maria Giovana Borges Saidel; Eduardo Sodre de Souza; Débora de Souza Santos (Nursing Reports)
Introduction: The health education curricula should explicitly recognize, define, and address the unique needs and health disparities faced by Black and LGBTQIA+ populations, as a means of ensuring that healthcare for these populations is both comprehensive and inclusive. Aim: To map scientific evidence and identify knowledge gaps regarding the health of Black and LGBTQIA+ populations within the global context of health education. Methods: A scoping review will be conducted following the JBI methodology. The articles will be retrieved from Scopus, Web of Science, PubMed, Embase, MEDLINE, BVS, CINAHL, ERIC, Cochrane, BDTD, PQDT, EBSCO, and NDLTD. The search will be conducted without language or time restrictions. Two independent reviewers will screen the studies and extract data using a form specifically developed for this purpose. The concepts, definitions, structures, results, and applications of professional health education worldwide for the healthcare of Black and LGBTQIA+ populations will be summarized and discussed. Inclusion Criteria: Studies related to professional health training at both undergraduate and graduate levels, as well as other educational modalities that address the provision of healthcare for these populations, will be included. The results will be presented in both tabular and graphical formats, accompanied by a narrative summary. Protocol registered in the Open Science Framework (OSF).